Revitalizing the Malay Language in Higher Education: A Study of Intercultural Learning Materials in Rokan Hulu - Eripuddin; Yahya, Rosatiqah Binti; Abdullah, Fazlina Shasa Binti (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2025)
This study aims to examine the impact of intercultural learning materials on student engagement, language retention, and proficiency in Malay. Using a mixed-methods design, data were collected from 120 students and 10 instructors in Rokan Hulu Regency through surveys, interviews, classroom observations, and material analysis. The surveys explored students’ linguistic challenges and cultural exposure, while interviews gathered instructors’ perspectives on pedagogy. Observations assessed engagement in classrooms with varying degrees of intercultural integration, and content analysis identified gaps in the representation of cultural narratives. Quantitative data were analyzed statistically, and qualitative data underwent thematic coding.The findings show that students with limited intercultural exposure often rely on regional dialects or English, struggling with formal Malay. Conversely, classrooms that incorporated intercultural learning materials—including digital storytelling, folklore, and historical narratives—demonstrated higher participation and improved fluency. Instructors criticized rote learning methods and emphasized the need for immersive, culturally enriched instruction. The study concludes that integrating intercultural learning materials, multimedia tools, and experiential learning strategies can enhance Malay language acquisition. These findings provide valuable implications for curriculum development, underscoring the role of culturally responsive pedagogy in fostering meaningful and sustainable language learning within a globalized educational landscape.